Carcinoma stomach with intestinal non-rotation: An unusual case report - Kalyan Pandey; Basavaraj Patil; Padmalaya Devi; P K Das (Indian Journal of Case Reports, 2020)
Gut malrotation or non-rotation is mainly a problem of the pediatric age group, however, adult and late adult presentation are not rare. Various cases of gastrointestinal malignancies associated with gut malrotation have been reported in the past. The true association between these two entities is unknown. This is one such rare case of carcinoma stomach associated with intestinal non-rotation in an adult patient. The patient was asymptomatic of non-rotation but developed symptoms of carcinoma of the stomach and non-rotation were diagnosed incidentally. The patient was treated for carcinoma and prophylactic appendectomy was done and non-rotation was left untouched.